Can Basel II enhance financial stability? A pessimistic view - L. Randall Wray (Levy Economics Institute of Bard College, 2006)
Even as the United States enjoys an economic expansion, there is an undercurrent of concern among economic analysts who follow financial markets. Some feel that the expansion of the credit derivatives markets poses the threat of a crisis similar to the Long-Term Capital Management debacle of 1998. Credit derivatives allow banks to share risks with holders of the derivatives, which are often mutual funds and other nonbank financial institutions.The Basel II Accord, now being implemented in many countries, is hailed as a good form of protection against the risk of a series of bank failures of the type that might cause problems in the derivatives markets. Basel II represents a more sophisticated and complex version of the original Basel Accord of 1992, which set minimum capital ratios for various types of bank assets.
Keywords: 330; Bankenliquidität; Bankenkrise; Bankrisiko; Bankenaufsicht; Bankenpolitik; Internationaler Finanzmarkt; Welt; Basel II